1981
DOI: 10.1159/000149210
|View full text |Cite
|
Sign up to set email alerts
|

Structural Proteins and Glycoproteins of Infectious Bronchitis Virus Particles Labeled during Growth in Chick Embryo Cells

Abstract: Seven Australian infectious bronchitis viruses incorporated radioactive amino acid label during growth in two types of cell culture. From purified virions, four major polypeptides of molecular weights 91,000 (GP91), 51,000 (VP51), 25,000 (GP25) and 23,000 (VP23) were separated by PAGE. Two minor polypeptides of molecular weights 210,000 (GP210) and 185,000 (GP185) were also identified. 3H-glucosamine was incorporated during growth of virus into GP210, GP185, GP91 and GP25. Bromelain digestion of virions remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Competitive ABAs were used for the topographical analysis. The Mr of the proteins precipitated by the various MAbs corresponded to the published Mr of structural proteins of IBV (Cavanagh, 1981;Lomniczi & Morser, 1981 ;Wadey & Westaway, 1981 ;. In addition to a nucleoprotein with an Mr of 49 000, MAb 26.2 precipitated a 45K protein and small amounts of a 39K protein.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Competitive ABAs were used for the topographical analysis. The Mr of the proteins precipitated by the various MAbs corresponded to the published Mr of structural proteins of IBV (Cavanagh, 1981;Lomniczi & Morser, 1981 ;Wadey & Westaway, 1981 ;. In addition to a nucleoprotein with an Mr of 49 000, MAb 26.2 precipitated a 45K protein and small amounts of a 39K protein.…”
Section: Discussionmentioning
confidence: 71%
“…The structural proteins of IBV are a phosphorylated nucleoprotein with an Mr of 56000 (56K), a membrane protein that is heterogeneously glycosylated with an Mr ranging from 23000 to 36000 and two glycoproteins, S1 and $2, with an Mr of 92000 and 84000 respectively (Lanser & Howard, 1980;Cavanagh, 1981 ;Lomniczi & Morser, 1981;Wadey & Westaway, 1981;. The spikes or peplomers of IBV are formed from two or three copies each of S 1 and $2 (Cavanagh, 1983a).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the largest glycoproteins of TCV appear to differ fundamentally fi'om those of the well-characterized MHV and IBV viruses. Whereas the largest peplomeric glycoproteins of these two viruses are not changed by the action of reducing agents such as 2-mercaptoethanol [4,32,33,38], the 140,000 tool. wt.-protein of TCV appeared to be reduced to a presumptive 66,000 subunit.…”
Section: Discussionmentioning
confidence: 97%
“…Two of these, S and M, are glycosylated (Cavanagh, 1981;Lomniczi & Morser, 1981 ;Wadey & Westaway, 1981 ;Stern et al, 1982). My studies of IBV have indicated that the surface projections are associated with two glycopolypeptides, S1 (90K; K = 1000 daltons) and $2 (84K), and that the M protein was associated with two glycopolypeptides of 30K and 28K (Cavanagh, 1981); SI had previously been assigned a mol.…”
Section: Discussionmentioning
confidence: 99%